Decoding the consumer mindset: Exploring the role of e-WOM, online experiences and brand trust in KKV one-stop shop purchase intention - Erawati, Sherly Hesti; Rahmawati, Rina (International Journal of Scientific Research and Management (IJSRM), 2024)
This quantitative study aims to contribute to this body of knowledge by investigating the influence of e-WOM, online shopping experiences and brand trust on purchase decisions at KKV one-stop shopping store, a prominent e-commerce platform specializing in one-stop shopping. By examining the roles of e-WOM, online experiences, and brand trust in shaping consumer mindsets and purchase decisions at KKV one-stop shopping store, this study aims to contribute to the growing body of knowledge in consumer behavior and e-commerce research, particularly in the context of one-stop shopping platforms. Primary data were collected through a questionnaire distributed through social media platforms using the Google Form application. The study used a purposive sampling technique and the final sample consisted of 121 respondents. The results show that e-WOM, online shopping experience and brand trust have positive and statistically significant effects on purchase decisions. Specifically, favorable e-WOM communication, positive online shopping experience and high levels of brand trust increase the likelihood that consumers will purchase from KKV one-stop shopping store. The findings highlight the importance of cultivating positive e-WOM, providing seamless online shopping experiences and fostering brand trust as strategies to improve consumer purchase decisions in the e-commerce space.